Pannexin 3 is required for late stage bone growth but not for initiation of ossification in avian embryos. Issue 9 (25th July 2016) - Bond, Stephen R.; Abramyan, John; Fu, Kathy; Naus, Christian C.; Richman, Joy M.
Abstract : Background: Pannexin 3 (PANX3) is a channel‐forming protein capable of stimulating osteogenesis in vitro. Here, we studied the in vivo roles of PANX3 in the chicken embryo using the RCAS retroviral system to over‐express and knockdown expression during endochondral bone formation.Results: In the limbs, PANX3 RNA was first detected in the cartilage condensations and became restricted to the prehypertrophic cartilage of the epiphyses, diaphysis, and perichondrium. The increase in PANX3 was not sufficient to alter osteogenesis; however, knockdown with a virus containing an interference RNA construct caused a 20% reduction in bone volume. The control virus containing an shEGFP cassette did not affect development. Interestingly, the phenotype was restricted to later stages rather than to proliferation of the skeletogenic mesenchyme, formation of the cartilage condensation, or creation of the hypertrophic zones. In addition, there was also no change in readouts of Hedgehog, WNT, fibroblast growth factor, or bone morphogenetic protein signaling using either quantitative real‐time polymerase chain reaction or radioactive in situ hybridization.Conclusions: Based on the normal expression domains of PANX3 and the relatively late manifestation of the phenotype, it is possible that PANX3 hemichannels may be required to facilitate the transition of hypertrophic chondrocytes to osteoblasts, thereby achieving final bone size. Developmental Dynamics 245:913–924, 2016 . © 2016 Wiley Periodicals, Inc.